Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Loyalitas Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi: Studi Kasus pada Divisi Valve PT Metal Castindo Industritama - Inez Delia Saputri; Anita Novialumi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Employee loyalty is an important factor in supporting the achievement of organizational goals and company sustainability. Low loyalty can have an impact on decreased productivity, weakened organizational commitment, and increased employee desire to leave the company. This study aims to analyze the effect of work motivation and work environment on employee loyalty with job satisfaction as a mediating variable in the Valve Division. The study used a quantitative approach with data collected through distributing questionnaires to 72 employees. Data analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4.1.1.8 software. The results of the study indicate that work motivation and work environment have a positive and significant effect on job satisfaction and employee loyalty. In addition, job satisfaction is proven to have a positive and significant effect on employee loyalty and is able to mediate the influence of work motivation and work environment on employee loyalty. These findings indicate that increasing work motivation and creating a conducive work environment can increase job satisfaction which ultimately strengthens employee loyalty to the company.